Clinical characteristics and outcomes of hospitalized patients with intracranial hemorrhage after percutaneous coronary intervention - Zhou, Yujing; Su, Xin; Liu, Peng; Tang, Yi; Cheng, Dong; Li, Haiyu; Sang, Haiqiang (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesComplications of intracranial hemorrhage (ICH) after percutaneous coronary intervention (PCI), although rare, have a poor prognosis with high mortality rates. This study aims to provide information on the clinical characteristics and outcomes of hospitalized patients with ICH after PCI.Materials and methodsThis retrospective study included 24 patients enrolled from February 2014 to September 2023, which occurred ICH during post-PCI hospitalization. We mainly analyzed general, procedural, ICH features and subsequent outcomes. In addition, the predictive ability of the CRUSADE, ARC-HBR, and ACUITY scores was assessed with the receiver operating characteristics area under the curve (AUC).ResultsAmong the 24 patients, the mean age was 62.21 ± 10.01 years, and 66.7% (n = 16) were men. The mortality of ICH patients after PCI was very high (n = 13, 54.2%). In addition, the most common initial manifestation of ICH patients was the disturbance of consciousness (n = 14, 58.3%). Over half of the cases (58.3%) occurred ICH within the first 12 h following PCI. 13 patients (54.2%) had an ICH volume ≥30 cm3, and of these patients, a total of 11(84.6%) died. ICH volume ≥30 cm3 (p = 0.038), and the use of mechanical ventilators (p = 0.011) were significantly higher in patients who died. The AUC of CRUSADE, ARC-HBR, and ACUITY scores were 0.500, 0.619, and 0.545, respectively.ConclusionsIn our study, the mortality of ICH after PCI was high. The high volume of ICH indicates a high risk of death.